Efficiencies of State Police in India and Significant factors Effecting (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper focuses on the factors that effects the efficiency of the State Police in India. The work performed in this paper is on secondary data and the data were collected from the sites of Bureau of Police Research and National Crime Record Bureau. This study aims to examine the factors that effects relative efficiency of state police units in India for the year 2019. The relative efficiency of the State Police is calculated by the Data Envelopment Analysis and Probit model is used in obtaining the factors affecting the efficiencies of state police.